Producción de colonias en Abejas Africanizadas (Apis mellifera L.) mediante Métodos de División de Núcleos en un colmenar del distrito Pinto Recodo - Lamas - Gómez Shapiama, Gilberto (2006)
Present work took effect in the lng Goethe Angulo González’s apiary, in the country experimental rustic farm Chingay: once 23 was located in Pinto Recodo provincia's distrito of Lamas and departamento of San Martin, his geographic position to 060 40 southem latitude 760 37 00 longitud Oeste to 400 msnmm's altitude. Under half way environmental conditions controlled, in junio's period to octubre's month of the 2005, for the sake of evaluating 04 increment methods of population of bees africanízed (Apia mellifera L); in hives in production. Treatments were four. With three repetitions each of them distribution once was accomplished at random and painted in colors enumeration different to tell apart distinct treatments. Evaluations are developed in 10x10cm's dimension; coming from cone 1 lay the foundations of the wax's dimension stamped measure 40x20cm. Evaluation will develop: start day of posture of the queen, number of eggs of workwomen per day of the queen, larvas's number of workwomen, cold sores number workmomen's operculadas and population's relative quantity of adults, his analysis studies statistical for each one of them. With the intervals in days 7, 15 and 30 days after initiate the posture. The aftermaths he allowed us to obtenidos to have a clearing once the treatment that offers giving one as recommendation the best-suited methods in order to the populations's development and 1 increment of bigger hives number in short periods was resulted from.